Reactive power allocation for loss minimisation in a stand alone variable speed constant frequency double output induction generator - Bagarty, Durgesh Prasad; Kastha, Debaprasad (IET power electronics, 2013)
Vector control algorithms reported so far for stand alone operation of variable speed constant frequency double output induction generators propose to supply the full magnetisation current of the machine in addition to the torque producing component from the rotor side converter. As the rotor of a normal induction machine is not designed for this additional load this approach leads to underutilisation of the machine torque capacity. Moreover, supplying the entire magnetisation current from the rotor side is not optimal from the point of view of the machine losses. Since the load voltage is regulated by manipulating the magnetising current through a slow acting flux control loop undesirable fluctuations in the load voltage waveforms are observed during fast load transients. An improved stator flux oriented control strategy for this type of generators, proposed in this study, eliminates undesirable load voltage transients by directly regulating the stator flux through the stator side converter. The total reactive power demand of the system is dynamically distributed between the two converters according to an optimum allocation program so as to minimise the losses without disturbing the stator flux. The effectiveness of the proposed algorithms is verified experimentally on a laboratory prototype.